Study of Oil Content in Fruits of Wild Olive (Olea caspidata Wall.Ex.G.Don) and Its Potential Commercialization in Nepal - Bhandari, Netra Lal; Chhetri, Krishna Bahadur Kunwar; Pandey, Durga Prasad; Nayak, Kanchan Kumar (Journal of Nepal Chemical Society, 2017)
available with fulltext.